Rediscovery and lectotypification of Phyllanthus megacarpus (Phyllanthaceae), an endemic species from the Western Ghats, India - Ravikumar, K.; Gnanasekaran, G.; Tiwari, Umeshkumar (Rheedea, 2015)
Phyllanthus megacarpus (Gamble) Kumari & Chandrab., a narrow endemic species has been rediscovered after a lapse of 130 years from other than its type locality, which also forms an addition to the flora of Karnataka. Besides, the name Phyllanthus megacarpus (= Reidia megacarpa Gamble) is lectotypified here.